#### Answer

$(\displaystyle \frac{1}{2},\frac{1}{2})$

#### Work Step by Step

Isolate $y$ in eq.$2$
$ 3x-y=1\qquad$ ... add $y-1$
$3x-1=y$
$ y=3x-1\qquad$ (*)
Replace $y$ with $3x-1$ in the other equation:
$ 2x+2(3x-1)=2\qquad$ ... and solve for $x$. Simplify
$2x+6x-2=2$
$ 8x-2=2\qquad$ ... add 2
$8x=4$
$x=\displaystyle \frac{1}{2}$
Now, back-substitute into (*)
$y= 3(\displaystyle \frac{1}{2})-1=\frac{1}{2}$
Form an ordered pair $(x,y)$ as the solution to the system
$(\displaystyle \frac{1}{2},\frac{1}{2})$